Plant Science 2012
DOI: 10.5772/53694
|View full text |Cite
|
Sign up to set email alerts
|

Microalgal Biotechnology: Prospects and Applications

Abstract: Plant Science 276composition, pigments and different constituents which may vary with salt stressed culture conditions and describe the antioxidant characteristics of algae. What are microalgae?Microalgae are prokaryotic or eukaryotic photosynthetic microorganisms that produce carbohydrates, proteins and lipids as a result of photosynthesis. They can grow rapidly and live in harsh conditions due to their unicellular or simple multicellular structure. Examples of prokaryotic microorganisms are Cyanobacteria (Cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 117 publications
0
9
0
Order By: Relevance
“…PUFAs are classified as n-3 and n-6 and play an important role in human and animal nutrition [41,42]. It is reported that n-3 fatty acids play an important role in the prevention of coronary heart disease and inflammatory disease, brain disorder, such as Alzheimer's disease and help in cancer therapy [43][44][45], while n-6 fatty acids are pro-inflammatory [41,46]. The functional sources of n-3 in microalgae are normally eicosapentaenoic (EPA, C20:5n-3) and docosahexaenoic (DHA, C22:6n-3) acids; however, chlorophytes and particularly freshwater microalgae are, in general, deficient in both C20 and C22 PUFAs [4,45].…”
Section: Proximate Compositionmentioning
confidence: 99%
See 2 more Smart Citations
“…PUFAs are classified as n-3 and n-6 and play an important role in human and animal nutrition [41,42]. It is reported that n-3 fatty acids play an important role in the prevention of coronary heart disease and inflammatory disease, brain disorder, such as Alzheimer's disease and help in cancer therapy [43][44][45], while n-6 fatty acids are pro-inflammatory [41,46]. The functional sources of n-3 in microalgae are normally eicosapentaenoic (EPA, C20:5n-3) and docosahexaenoic (DHA, C22:6n-3) acids; however, chlorophytes and particularly freshwater microalgae are, in general, deficient in both C20 and C22 PUFAs [4,45].…”
Section: Proximate Compositionmentioning
confidence: 99%
“…Lutein is largely consumed as a feed additive in aquaculture and as a food colorant. Despite this, as it is an essential component for the macula lutea in the eye retina and lens, and since lutein from microalgae (E161g) was approved as a color additive in the EU and USA, another feasible application might be within the realm of the pharmaceutical industry [10,44,50]. In the eastern world, the percentage of people with Age-Related Macular Degeneration (ADM) disease is high and the recommended intake of lutein is 6 mg daily, which might often be achieved via ingestion of food supplements [44,50].…”
Section: Pigment Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microalgae are autotrophic microorganisms, which are able to produce biomass from solar energy, CO 2 and nutrients, with higher photosynthetic activity compared to terrestrial plants [1,2]. Resulting biomass includes important metabolites such as carbohydrates, lipids, proteins and also many other bioactive compounds like pigments and phenolics.…”
Section: Introductionmentioning
confidence: 99%
“…They are predominantly aquatic and microscopic and are considered a very heterogeneous group of microorganisms. They have the potential to produce various biomolecules such as lipids, carbohydrates, and proteins and are used in the pharmaceutical and food industries (Mostafa, 2012).…”
Section: Introductionmentioning
confidence: 99%